5% Lidocaine Medicated Plaster Use in Children with Neuropathic Pain from Burn Sequelae. Issue 3 (28th December 2012) - Orellana Silva, Matias; Yañez, Veronica; Hidalgo, Gabriela; Valenzuela, Fernando; Saavedra, Rolando
Abstract Objective Neuropathic pain is a challenge in children with burn sequelae. Although relatively infrequent, the intensity and chronicity of neuropathic pain negatively impact functionality and quality of life. The use of 5% lidocaine medicated plaster has not previously been reported in children. We explored the effectiveness and safety of 5% lidocaine medicated plaster to treat neuropathic pain in children with burn sequelae. Design Three‐month prospective, uncontrolled study. Setting Corporation of Aid to Burned Children (COANIQUEM), a nonprofit pediatric burn rehabilitation center in Chile. Subjects Fourteen pediatric patients with burn sequelae neuropathic pain. Outcome Measures Demographics, burn and pain evolution (type, intensity [using Wong‐Baker FACES], and Douleur Neuropathique 4 [DN4]), and patient functionality. Plasma lidocaine levels were measured at 0, 12, 36, and 60 hours after treatment commencement. Results Fourteen patients were evaluable for plasma lidocaine levels. Twelve patients were available for clinical assessment (two patients lost to follow‐up) [mean (standard deviation)]: age, 11 years 7 months (2 years 6 months); weight, 45 kg (11.9 kg); burn evolution, 5 years 6 months (4 years); time between burn and pain onset, 3 years 6 months (3 years 2 months); time between pain onset and treatment, 5.1 months (4.8 months); lidocaine, between < and ½ plaster; initial pain intensity (FACES), 6.8 (1.6); final pain intensity, 0 in 11/12 patients; DN4, initial‐6, final‐2.3. All patients reported improved functionality. Plasma lidocaine levels were ≤27.45 ng/mL (>180 times below critical levels). No adverse reactions occurred. Conclusions These are the first published data suggesting that 5% lidocaine medicated plaster improves patient functionality, and is effective and safe for the treatment of neuropathic pain in pediatric patients with burn sequelae.